2015
DOI: 10.26719/2015.21.11.828
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of multidrug resistant Acinetobacter baumannii isolated from clinical specimens at King Hussein Medical Centre, Jordan: a retrospective analysis

Abstract: This study was conducted to determine the prevalence and the local antibiogram of multidrug-resistant Acinetobacter baumannii isolates in Al-Hussein Hospital at King Hussein Medical Centre in Amman, Jordan. In a retrospective study from January to December 2013, data on 116 non-repetitive positive clinical samples were retrieved from patients' laboratory records. The resistance rates of A. baumannii isolates were high for ceftriaxone, cefotaxime and ticarcillin (100%), ceftazidime, cefepime and piperacillin (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
4
6
1
Order By: Relevance
“…Developing of multi-drug resistant A. baumannii in the hospital could be due to lack of proper infection-control performance, the patient's normal bacterial flora under the aggressive antibiotics, or contaminated instruments, and overcrowding situations in the hospitals. In the present study, the higher rate of A. baumannii was found in male compared to females as in Table 2, 3, which is in agreement with observations in previous studies due to their exposing to the bacteria in environments (Oncul et al, 2009, Batarseh et al, 2015, Hatami, 2018. The predominance of male patients infected with Acinetobacter has been confirmed in other studies but the cause is not justified (Uwingabiye et al, 2016).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Developing of multi-drug resistant A. baumannii in the hospital could be due to lack of proper infection-control performance, the patient's normal bacterial flora under the aggressive antibiotics, or contaminated instruments, and overcrowding situations in the hospitals. In the present study, the higher rate of A. baumannii was found in male compared to females as in Table 2, 3, which is in agreement with observations in previous studies due to their exposing to the bacteria in environments (Oncul et al, 2009, Batarseh et al, 2015, Hatami, 2018. The predominance of male patients infected with Acinetobacter has been confirmed in other studies but the cause is not justified (Uwingabiye et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the resistance rate of isolates to colistin was (0%), studies in Turkey and Iran (Ozdemir et al, 2011, Sarhaddi et al, 2017, reported the antibiotics with the highest in vitro susceptibility was colistin, 100 % susceptible against A. baumannii other data reported from Jordan (1.7%), and (0.5%) in Saudi Arabia (Batarseh et al, 2015, Al-Mously, 2013. In contrast, a study from Iran (Sepahvand et al, 2015) reported that 6% of the isolates were resistant to colistin which was a higher rate of resistance when compared with our result.…”
Section: Resultssupporting
confidence: 54%
“…The rate of CRAB in our country is close to that of areas as remote as Jordan (97·4%) (Batarseh et al . ), but exceeded the rates described above and that reported in other Middle East countries such as Syria (64·4%) (Hamzeh et al . ), Saudi Arabia (32·6–51·9%) (Abdalhamid et al .…”
Section: Resultscontrasting
confidence: 52%
“…This pattern of antibiotic resistance often varies with time and from one area to another or even within the same area. 3,4 Nowadays, in developing countries, including Iran, physicians face serious challenges to the treatment of patients infected with MDR A. baumannii, presenting severe healthcare problems owing to treatment failure. 5,6 Carbapenem antibiotics, such as imipenem and meropenem, are the most effective therapeutic options for A. baumannii infections.…”
Section: Introductionmentioning
confidence: 99%